ANALISIS EFEKTIVITAS AUGMENTED REALITY TERHADAP KETERAMPILAN BERPIKIR KOMPUTASIONAL SISWA: SEBUAH TINJAUAN SISTEMATIS - Indah Febrianur (STKIP Subang, 2026)
The rapid development of digital technology in education has encouraged the integration of innovative learning approaches to enhance 21st-century skills, particularly computational thinking. Augmented Reality (AR), as an interactive visual technology, is considered to have significant potential in supporting more contextual, engaging, and meaningful learning experiences. This study aims to analyze the effectiveness of Augmented Reality in improving students’ computational thinking skills through a systematic literature review approach. The method employed is a Systematic Literature Review (SLR) by examining scholarly articles published between 2018 and 2025 from various relevant academic databases. The literature selection process was conducted based on predefined inclusion and exclusion criteria to ensure the quality and relevance of the selected studies. The findings indicate that the use of AR in learning contributes positively to the development of computational thinking skills, particularly in terms of problem decomposition, pattern recognition, abstraction, and algorithm design. In addition, AR enhances student engagement and learning motivation by providing interactive and immersive learning experiences. However, several challenges remain, including limited technological infrastructure and teachers’ readiness in implementing AR-based learning. Therefore, further support is required to optimize the integration of AR technology in educational settings.